2016
DOI: 10.3310/hsdr04350
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for models of diagnostic service provision in the community: literature mapping exercise and focused rapid reviews

Abstract: BackgroundCurrent NHS policy favours the expansion of diagnostic testing services in community and primary care settings.ObjectivesOur objectives were to identify current models of community diagnostic services in the UK and internationally and to assess the evidence for quality, safety and clinical effectiveness of such services. We were also interested in whether or not there is any evidence to support a broader range of diagnostic tests being provided in the community.Review methodsWe performed an initial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 292 publications
1
6
0
Order By: Relevance
“…These have also been fulfilled. Lastly, as per global standards, medical imaging units require necessary drainage of sewage to dump the chemicals and patient waste products, and this requirement has been complied with in all units [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…These have also been fulfilled. Lastly, as per global standards, medical imaging units require necessary drainage of sewage to dump the chemicals and patient waste products, and this requirement has been complied with in all units [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…We introduce a mixed approach method combining facility-based ultrasound service delivery, a component where women access ultrasound in the health facility, and a facility outreach model where the ADM maintain a booking schedule in health facility other than their own on a fixed routine. Chamber and Boothe [3] argue that health administrations aiming to institutionalize facility outreach and community-based model should put in place policy guidance, primarily to account for inappropriate utilizations of scanning services. Such administrations should also have a clear clinical justification, action guidelines to avoid over treatment and have a patient care guideline to manage anxiety and a referral framework for altered case management.…”
Section: Discussionmentioning
confidence: 99%
“…GPs with specialist interests (GPwSIs) 71,173,174 or the relocation of services from secondary care to primary care settings). [174][175][176][177][178] More recently, the ways in which specialist care is being implemented in primary care go beyond the 'drag and drop' approach of simply relocating a hospital outpatient clinic into a community setting; instead, methods that put education at the core alongside the redesign of the patient pathway and/or the role of the professional are becoming more established. 179 Examples included in a recent The King's Fund report, Specialists in Out-Of-Hospital Settings: Findings from Six Case Studies, 179 are outreach clinics jointly staffed by hospital consultants and other health-care professionals, consultant-run e-mail and telephone helplines, consultant participation in MDT meetings, consultant-run education sessions and consultants supporting staff to work in extended roles.…”
Section: Characteristics Of Community-based Care and Primary Care Accessmentioning
confidence: 99%
“…164,181 In general, studies reporting on the transfer of care from secondary to primary care have reported that the quality of care achieves an acceptable standard. 71,173,174 The safety of diagnostic services transfer is equivocal; a literature-mapping exercise 175 found evidence that the quality (including diagnostic accuracy and the appropriateness of test ordering) and safety of diagnostic service provision in the community is mixed.…”
Section: Population Healthmentioning
confidence: 99%